The Incident Prevalence of 4T High Risk Pregnant Women - Dwi Linda Sari; Endah Mulyani (STIKes Patria Husada Blitar, 2023)
Pregnancy is a physiological condition, but pregnancy can also become pathological when accompanied by high-risk conditions. Restful (high risk) pregnancies are found in pregnant women who are too old, too young, too many and too close (4T). The aim of this research was to determine the prevalence of 4T high risk pregnant women in Gresik Regency. The type of research used quantitative descriptive with a survey research design. The population in this study was all 6,929 pregnant women in Gresik Regency. The results of this study showed that the highest incidence of 4T in pregnant women in Gresik Regency was at ages over 35 years, amounting to 22.7%, which occurred in Gresik District. Health workers are expected to pay more attention to the problems they face, to prevent problems that can increase maternal mortality.